The family: a key element in the education of students with special educational needs. (Journal of Parents and Teachers, 2014)
Parents should be involved in the educational process of their children, particularly those with special educational needs. The family has to collaborate, therefore, with the teachers, to promote the integral development of their children.
Keywords: Families; participation in the educational system; children with special educational needs.